Compounds in Human Body Organic (Eurasian Journal of Research, Development and Innovation, 2024)
This research includes an introduction to organic chemistry in the human body, compounds, their importance, composition, types and presence , the functional group is a group of atoms linked by strong covalent bonds and tending to function in chemical reactions as a single unit. You can think of functional groups as tightly knit “cliques” whose members are unlikely to be parted. Five functional groups are important in human physiology; these are the hydroxyl, carboxyl, amino, methyl and phosphate groups